Suppression of glioblastoma by targeting the overactivated protein neddylation pathway. Issue 10 (22nd April 2015) - Hua, Wei; Li, Chunjie; Yang, Zixiao; Li, Lihui; Jiang, Yanan; Yu, Guangyang; Zhu, Wei; Liu, Zhengyan; Duan, Shengzhong; Chu, Yiwei; Yang, Meng; Zhang, Yanmei; et al.
Abstract: Background: The neddylation pathway has been recently identified as an attractive anticancer target, and MLN4924, a specific NEDD8-activating enzyme inhibitor, has been developed as a first-in-class anticancer agent. However, neither the status of the neddylation pathway in glioblastoma (GBM) nor the effect of MLN4924 against GBM has been systematically investigated yet. Methods: To measure the activation state of the neddylation pathway in GBM, expression of the NEDD8-activating enzyme (E1), NEDD8-conjugating enzyme (E2), and global protein neddylation in GBM tumor tissues versus adjacent tissues were examined by immunoblotting analysis and immunohistochemistry staining. To assess the therapeutic efficacy of neddylation inhibition in GBM, cell proliferation in vitro and tumor growth in vivo were determined upon neddylation inhibition by MLN4924, an investigational NEDD8-activating enzyme inhibitor. Results: The neddylation pathway was overactivated in a majority of GBM tumor tissues when compared with adjacent normal tissues. The upregulation of this pathway in GBM tissues was positively correlated with high-grade disease and postoperative recurrence but was negatively associated with patient overall survival. MLN4924 treatment inhibited cullin neddylation, inactivated cullin-RING E3 ligase, and led to the accumulation of tumor-suppressive cullin-RING E3 ligase substrates to trigger cell-cycle arrest and senescence or apoptosis in a cell-line dependent manner. Moreover, inhibition of neddylation by MLN4924 significantly suppressed tumor growth in an orthotopic xenograft model of human GBM. Conclusion: Our study indicates that an overactivated neddylation pathway may be involved in GBM progression and that inhibition of this oncogenic pathway is a potentially new therapeutic approach for GBM.